Application of screening methods for weight-loss compounds and identification of new impurities in counterfeit drugs. (October 2019) - Lee, Ji Hyun; Park, Han Na; Kim, Nam Sook; Park, Seongsoo; Bogonda, Ganganna; Oh, Kyungsoo; Kang, Hoil
Highlights: The 23 counterfeit weight-loss drugs were screened by UHPLC-PDA analysis. Five of samples were detected in range of 0.03–132.40 mg/g. Three unknown compounds in one sample were structurally elucidated by LC-HR–MS and NMR. They were first detected in counterfeit drugs and identified as phenolphthalein impurities. These impurities were possibly produced during the synthesis of phenolphthalein. Abstract: With the increasing prevalence of obesity, the use of counterfeit drugs for weight loss is widespread owing to their easy and rapid availability. Since counterfeit weight-loss drugs are not prepared under the rigorous standard of Good Manufacturing Practice (GMP), they pose a risk to public health and cause significant side effects. To counteract the risk posed by counterfeit drugs, we investigated counterfeit weight-loss drugs seized by the Incheon Customs Services using UHPLC-PDA. Five of 23 confiscated samples with distinctive pink-coloured coating contained levothyroxine, sennoside A and B, and phenolphthalein in amounts ranging from 0.03–132.40 mg/g. In addition, three unknown compounds in one of the adulterated samples containing phenolphthalein were structurally elucidated by several analytical techniques. Their accurate masses corresponded to molecular formula of C34 H22 O7, C34 H20 O6, and C20 H12 O3, respectively. These compounds were identified as impurities, possibly produced during the synthesis of phenolphthalein or by improper removal during purification. These impurities were detected for the first time in counterfeit drugs.